2004
DOI: 10.5547/issn0195-6574-ej-vol25-no3-5
|View full text |Cite
|
Sign up to set email alerts
|

Trading in the Downstream European Gas Market: A Successive Oligopoly Approach

Abstract: A model of successive oligopoly is applied to the European natural gas market. The model has a two-level structure, in which Cournot producers are also Stackelberg leaders with respect to traders, who may be Cournot oligopolists or price takers. Several conclusions emerge. First, successive oligopoly ("double marginalization") yields higher prices and lower consumer welfare than if oligopoly exists only on one level. Second, due to the high concentration of traders, prices are distorted more by market power in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 21 publications
1
77
0
1
Order By: Relevance
“…Estrada and Fugleberg (1989), Al-Sahlawi (1989). Boots et al (2004) use elasticities from Pindyck (1979) which are considerably higher (between 1.17 and 2.23). 11 For more details about programmation in the MCP format see Rutherford (1995) and Ferris and Munson (2000).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrada and Fugleberg (1989), Al-Sahlawi (1989). Boots et al (2004) use elasticities from Pindyck (1979) which are considerably higher (between 1.17 and 2.23). 11 For more details about programmation in the MCP format see Rutherford (1995) and Ferris and Munson (2000).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, a number of simplifying assumptions, such as symmetry of traders, diminish the generality of this approach of double marginalization. Moreover, Boots et al (2004)assume the domestic production to be an exogenous value instead of including it in the optimization. Another difference with GASMOD (see details in section 3) is the use of cost functions and linear demand functions from Golombek et al (1995).…”
Section: State Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Pre-liberalization models were published by Golombek et al [30,31] to assess the potential impact of liberalization on the West European gas market. Follow up model setups were built by several groups of Dutch teams: ECN's GASTALE [32], CPB group's NATGAS [33], and TNO-NITG Thesis work ENETSIM [34]. The latter study used an agent-based economic optimization modeling framework following Tesfatsion [35], using a MATLAB model platform; the relevant algorithms appear in van Benthem ( [34], pp.…”
Section: European Gas Market Modelsmentioning
confidence: 99%
“…Thus, several models have indicated that market power is indeed an issue in the European natural gas market, amongst them Boots et al (2004), Egging and Gabriel (2006), and Egging et al (2008). Smeers (2008) summarized and discussed the papers that develop strategic models of European gas supply.…”
Section: Introduction: the European Natural Gas Marketmentioning
confidence: 99%